Conceptual Model for Organizational Citizenship Behavior in Improving Performance Based on Islamic Work Ethic Moderation - Zulfikar (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to identify the role of religiosity as measured by the variable Islamic work ethic in the relationship of OCB to performance and identify important antecedents that will motivate employees to engage in this behavior. We then provide a conceptual model that illustrates the sources and potential consequences of the behavior of organizational members. Resultsshows that there are several positive and significant antecedents of OCB, namely cultural changes, training, and reward systems. In addition, Islamic Work Ethic is a significant moderator of the relationship between OCB and Employee Performance.